2016
DOI: 10.1016/j.annemergmed.2016.08.189
|View full text |Cite
|
Sign up to set email alerts
|

176 The Asthma Mobile Health Study: Wildfires and Asthma Exacerbations, Just Blowing Smoke or is There a Correlation?

Abstract: Results: The median times for sham CT consent in phase 1 were 2 and 4 minutes. Of the 729 patients enrolled in phase 2, 647 (89%) underwent CT evaluation. Their median age was 52 years (IQR 32, 74); 54% were male; 95% had a blunt mechanism of trauma; 55% were admitted to the hospital; and 5% had a surgical procedure performed after CT. The median and mean TACCT were 11 min (IQR 7, 19) and 17 min (SD 20) respectively. The median GCS was 15 (IQR 14, 15). Of the 647 patients enrolled, 439 patients (67.9%; 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The Gan et al (2020) study found results of The Relationship Between Wildfires and Respiratory Health (Krishna Kolen) elevated office visits with elevations of wildfire smoke PM2.5 exposures and that these exposures had stronger impacts on females and those in the 15-65year-old age category. The Gowda et al (2016aGowda et al ( , 2016b studies demonstrated a close correlation between wildfire-induced air quality changes and users reporting air quality as an asthma trigger. Further, Haikerwal et al (2015) showed positive associations between wildfire related PM2.5 exposures and emergency department attendances for asthma, again with increased risk found for adult women and in same day exposures to PM2.5.…”
Section: Respiratory Implications As a Results Of Smoke Exposurementioning
confidence: 98%
See 4 more Smart Citations
“…The Gan et al (2020) study found results of The Relationship Between Wildfires and Respiratory Health (Krishna Kolen) elevated office visits with elevations of wildfire smoke PM2.5 exposures and that these exposures had stronger impacts on females and those in the 15-65year-old age category. The Gowda et al (2016aGowda et al ( , 2016b studies demonstrated a close correlation between wildfire-induced air quality changes and users reporting air quality as an asthma trigger. Further, Haikerwal et al (2015) showed positive associations between wildfire related PM2.5 exposures and emergency department attendances for asthma, again with increased risk found for adult women and in same day exposures to PM2.5.…”
Section: Respiratory Implications As a Results Of Smoke Exposurementioning
confidence: 98%
“…By following the trends of results found in the literature review, it is expected that communities in the GPAZ would see increased emergency department admissions and hospitalizations for asthma and COPD during periods of increased fine particulate matter (PM2.5) in the air, which can be linked to the presence of wildfire smoke. Potential implications for respiratory outcomes due to elevated AQHI values based on the literature review suggest increased asthma hospitalizations and emergency department visits (Borchers Arrigada et al, 2019), elevated office visits (Gan et al, 2020), increased reporting of asthma triggers (Gowda et al, 2016a(Gowda et al, , 2016b, and increases in emergency department attendees for asthma on the same day of smoke exposure (Haikerwal et al, 2015).…”
Section: Implications For Respiratory Healthmentioning
confidence: 99%
See 3 more Smart Citations